PENGAWASAN PENDIRIAN BANGUNAN MELALUI SISTEM PELAYANAN TERPADU SATU PINTU DI KABUPATEN BULUKUMBA PERSPEKTIF HUKUM ISLAM - Agustiawan, Agustiawan; Halimang, St.; Hisbullah, Hisbullah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2023)
This study aims to determine the effectiveness of supervising the construction of buildings with a one-stop integrated service system in Bulukumba Regency. This type of research is empirical legal research with a juridical and normative Shari'a approach. The results of the study show that the building construction supervision concept is applied by DPMPTSP Bulukumba with a system of building administration supervision, technical supervision, and imposing sanctions on development violations. In reality, supervision of building construction in Bulukumba Regency is still not running effectively due to the lack of Human Resources and public awareness. In the view of Islamic law, supervision of building construction in Bulukumba Regency does not contradict Islamic law, DPMPTSP has carried out its obligations as a supervisory institution based on applicable legal rules.